2012
DOI: 10.1007/978-3-642-31424-7_29
|View full text |Cite
|
Sign up to set email alerts
|

Formal Verification and Validation of ERTMS Industrial Railway Train Spacing System

Abstract: Abstract. Formal verification and validation is a fundamental step for the certification of railways critical systems. Many railways safety standards (e.g. the CEN-ELEC EN-50126, EN-50128 and EN-50129 standards implement the mandatory safety requirements of IEC-61508-7 standard for Functional and Safety) currently mandate the use of formal methods in the design to certify correctness. In this paper we describe an industrial application of formal methods for the verification and validation of "Logica di Sicurez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 25 publications
0
21
0
2
Order By: Relevance
“…Prominent studies from the B community include [20,33,3] whilst [35,28] are classical contributions from process algebra and [10] uses techniques from Algebraic Specification. On a lower abstraction layer, [7,18,16,5] verify the safety of interlocking programs with logical approaches.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Prominent studies from the B community include [20,33,3] whilst [35,28] are classical contributions from process algebra and [10] uses techniques from Algebraic Specification. On a lower abstraction layer, [7,18,16,5] verify the safety of interlocking programs with logical approaches.…”
Section: Related Workmentioning
confidence: 99%
“…Ferrari et al [7] state that model checking large interlocking systems is infeasible with current state-of-the-art model checkers, in particular SPIN and NuSMV. However, Cimatti et al [5] have demonstrated considerable success using NuSMV on industrial scale problems. James et al [16] also demonstrate better results and the feasibility of the lower level approach involving program slicing.…”
Section: Verification Comparisonmentioning
confidence: 99%
“…Prominent studies from the B community include [17,18] whilst [19,20] are classical contributions from process algebra and [21] uses techniques from Algebraic Specification. On a lower abstraction layer, [22][23][24][25] verify the safety of interlocking programs with logical approaches.…”
Section: Related Workmentioning
confidence: 99%
“…control tables) by Haxthausen [30] also falls into the first category and is supported by automated tools that generate the models. Cimatti et al [25] also have had considerable success using NuSMV but their analysis is focussed on the implementation descriptions.…”
Section: Related Workmentioning
confidence: 99%
“…The results achieved are comparable in size to our Single Junction scenario. Cimatti et al [5] also have had considerable success using NuSMV but their analysis is focussed on the implementation descriptions.…”
Section: Related Workmentioning
confidence: 99%